Late mortality after bone marrow transplant for chronic myelogenous leukemia in the context of prior tyrosine kinase inhibitor exposure: A Blood or Marrow Transplant Survivor Study (BMTSS) report. Issue 22 (14th August 2019) - Wu, Jessica; Chen, Yanjun; Hageman, Lindsey; Francisco, Liton; Ness, Emily C.; Parman, Mariel; Kung, Michelle; Watson, James A.; Weisdorf, Daniel J.; Snyder, David S.; McGlave, Philip B.; Forman, Stephen J.; et al.
Abstract : Background: Late mortality was investigated in patients with chronic myelogenous leukemia (CML) who underwent blood or bone marrow transplant (BMT) with or without prior tyrosine kinase inhibitor (TKI) therapy. Methods: By using data from the Blood or Marrow Transplant Survivor Study, the authors examined late mortality in 447 patients with CML who underwent BMT between 1974 and 2010, conditional on surviving ≥2 years post‐BMT. For vital status information, the medical records, the National Death Index, and the Accurint database were used. Standardized mortality ratios (SMRs) were calculated using general population age‐specific, sex‐specific, and calendar‐specific mortality rates. Kaplan‐Meier techniques and Cox regression were used for all‐cause mortality analyses. Cumulative incidence and proportional subdistribution hazards models for competing risks were used for cause‐specific mortality analyses. Results: The 10‐year overall survival rate was 65.7% and 73% for those who underwent transplant with and without pre‐BMT exposure to TKI therapy, respectively. Patients who underwent transplant with and without pre‐BMT TKI experienced SMRs of 6.4 and 6.4, respectively ( P = .8); and the SMRs were 11.6 and 8.1, respectively, for those with high‐risk disease ( P = .2). Independent predictors of non–CML‐related mortality included chronic graft‐versus‐host disease (hazard ratio [HR], 2.8; 95% CI, 1.8‐4.4) and busulfan/cyclophosphamide conditioning (HR, 0.5; 95% CI, 0.3‐0.9; reference, total body irradiation/cyclophosphamide conditioning). The 20‐year cumulative incidence of CML‐related and non–CML‐related mortality was 6% and 36%, respectively, for the entire cohort. Both CML‐related mortality (HR, 1.0; 95% CI, 0.1‐12.6) and non–CML‐related mortality (HR, 1.3; 95% CI, 0.6‐3.1) were comparable for those with and without pre‐BMT TKI therapy. Conclusions: The similar late mortality experienced by patients with CML who undergo transplantation with or without pre‐BMT TKIs suggests that allogeneic BMT can be considered in the context of TKI intolerance or nonadherence. The prevention of post‐BMT non–CML‐related mortality could favorably affect long‐term survival. Abstract : Conditional on surviving for 2 years after bone marrow transplant (BMT), 10‐year overall survival is comparable for patients with chronic myelogenous leukemia (CML) who undergo transplant with and without pre‐BMT tyrosine kinase inhibitors (TKI). Non–CML‐related causes are the primary causes of death among patients with CML who survive for ≥2 years from BMT, irrespective of pre‐BMT TKI exposure.